Phase formation of hydroxyapatite particles at different calcination temperatures - S. Tigunta (2018)
Hydroxyapatite (HA) is classified as one of the important bioceramics, which has been used in orthopedics, medical and dental applications. It has bioactivity and good biocompatibility with the human organism, which is suitable in medical applications as an implant or coating on prostheses such as metal. In this study, the effects of calcinations temperatures on phase formation and physical properties of HA particles were investigated. The HA particles synthesized from bovine bone were cleaned and fired at 800 °C and subsequently ball milled for 24 h. Then received HA particles were divided into two parts. The first one was calcined at various temperatures from 900 to 1400°C and the second one was vibratory milled for 4 h and subsequently calcined at various temperatures from 900 to 1400°C. The calcined HA particles were characterized by X-ray diffraction (XRD) for their crystal structure and particle size analysis. Scanning electron microscope (SEM) was used for microstructural. © (2012) Trans Tech Publications.